Resternotomy, a single-center experience. (January 2017) - Salehi, Mehrdad; Bakhshandeh, Ali Reza; Saberi, Kianoush; Alemohammad, Mahmood; Sobhanian, Keivan; Karamnezhad, Maziar; Rigi, Farangis Sarouneh
Background: Reoperations are technically more difficult because of the risks associated with reentry in a heart with more advanced pathology, little reserve, and more frequent comorbidities. Routine peripheral cannulation before resternotomy is inadvisable, time-consuming, and has no noticeable role in decreasing the risks of reentry. We present our experience of resternotomy without routine peripheral cannulation. Methods: This was a retrospective study on 237 consecutive patients who underwent resternotomy between June 2011 and July 2013. Their mean age was 47.7 ± 18.2 years. We chose the best approach individually, according to lateral radiograph findings, patient risk factors, and previous surgery. Our goal was to observe events intraoperatively and their outcomes postoperatively. Results: Mean intensive care unit stay was 3.1 ± 0.9 days. Twenty-one (8.8%) patients died during their hospital stay. The most common cause of death was renal failure in 15 (71.4%) patients, coagulopathy in 4 (19%), and cardiac failure in 2 (9.5%). We had 3 right ventricular, one right atrial, one pulmonary artery, and 2 inferior vena caval tears during resternotomy and dissection; bleeding was controlled easily without peripheral cannulation. Femoral cannulation before resternotomy was performed in one patient who needed an emergency pulmonary embolectomy. Conclusions: Based on our experience, resternotomy with central cannulation is a safe strategy, and peripheral cannulation before resternotomy should be reserved for highly selected patients.